Has the Promise of the Internet Been Realized? Internet Access and Collective Invention among Independent and Organizational Patent Inventors. (December 2019) - Dahlin, Eric; Dufur, Mikaela; Flake, Dallan
The Internet provides individuals with new avenues for knowledge sharing and collaboration, two key ingredients for the production of novelty. Despite the unprecedented access to information and potential collaborators provided by the Internet, however, organizations remain the preeminent site of invention, presumably due to the tremendous resources, technology, and expertise at their disposal. Given the presumption that improved access to the Internet cultivates connectivity and novelty among individuals, on one hand, and the resources organizations can leverage to create novelty, on the other hand, we ask whether Internet access plays a role in the incidence of collective invention for independent inventors and organizational inventors in the knowledge economy. Regression models based on a sample of metropolitan areas in the United States predict that increases in household Internet access increases collective invention for organizational patent inventors, but not independent patent inventors.